2004
DOI: 10.1097/00008571-200410000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of aflatoxin-albumin adducts are associated with CYP3A5 polymorphisms in The Gambia, West Africa

Abstract: The CYP3A5 polymorphism is associated with increased levels of the mutagenic AFB1-exo-8,9-epoxide, particularly in individuals with low CYP3A4, and this may modulate individual risk of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 18 publications
5
25
0
1
Order By: Relevance
“…The functional CYP3A5 variant allele, CYP3A5*1 is the most frequent variant allele in the black population (B50%) 8,13,16 , whereas in Ethiopians, the defective variant allele (CYP3A5*3) is the most frequent allele (67%). The lower frequency of CYP3A5*1 and absence of the black population-specific allele, CYP3A5*7, differentiate Ethiopians from other black Africans and African Americans with respect to CYP3A5 allele frequency distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional CYP3A5 variant allele, CYP3A5*1 is the most frequent variant allele in the black population (B50%) 8,13,16 , whereas in Ethiopians, the defective variant allele (CYP3A5*3) is the most frequent allele (67%). The lower frequency of CYP3A5*1 and absence of the black population-specific allele, CYP3A5*7, differentiate Ethiopians from other black Africans and African Americans with respect to CYP3A5 allele frequency distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the genetic polymorphisms in CYP3A5 in African populations. 8,13,16 However, data from these studies cannot be extrapolated to other populations in the continent because Africans are heterogeneous with respect to pharmacogenetics of drug-metabolizing enzymes. 17,18 This study aimed at investigating the influence of CYP3A5 genotype and sex on the CYP3A phenotype and compared the use of plasma 4b-hydroxycholesterol and omeprazole to omeprazole sulfone ratio as CYP3A markers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the GSTM1-null should facilitate the formation of AFB1-DNA adducts in the cells. Several reports have shown that GSTM1 polymorphism is associated with the level of serum AFB1-albumin adducts [5,22,23] . For example, McGlynn et al [5] investigated the impact of this polymorphism on detoxification phenotype in 49 adult healthy males.…”
Section: Discussionmentioning
confidence: 99%
“…Kensler et al, (1998) found no association between AF-alb and GSTM1 genotype in adults from Qidong County, People's Republic of China. More recently, however, CYP3A5 genotypes associated with high expression were shown to have higher AF-alb levels in Gambian adults (Wojnowski et al, 2004).…”
Section: Human Variability and Factors Affecting Biotransformationmentioning
confidence: 98%